86 novel HLA‐E alleles discovered through full‐gene sequencing of 6227 hematopoietic cell transplant patients and unrelated donors. (20th November 2022) - Lucas, Jonathan A. M.; Georgiou, Xenia; Cooper, Michael A.; Robinson, James; Marsh, Steven G. E.; Mayor, Neema P.
Abstract : Until recently the number of alleles of the nonclassical HLA class I gene HLA‐E documented in the IPD‐IMGT/HLA Database was small and as a result, the gene was often not considered to be notably polymorphic. Here, we describe our work in identifying and submitting 86 novel HLA‐E alleles after full‐gene single‐molecule real‐time (SMRT) DNA sequencing of 6227 DNA samples. These samples were comprised of 2468 patients undergoing hematopoietic cell transplantation and 3759 unrelated potential donors. A total of 111 unique HLA‐E alleles were detected in this cohort. The majority of novel alleles (79.1%) contained polymorphisms in intronic regions, highlighting the significant undiscovered variation present in the noncoding regions of the HLA‐E gene.